Summer of hate - Kraus, Chris (Semiotext(e) native agents series, 2012)
Waking up from the chilling high of a near-death sex game, Catt Dunlop travels to Albuquerque in 2005 to reinvest some windfall real-estate gains and reengage with something approximating "real life." Aware that the critical discourse she has used to build her career as a visiting professor and art critic is really a cipher for something else, she hopes that buying and fixing slum buildings will bring her more closely in touch with American life than the essays she writes. In Albuquerque, she becomes romantically involved with Paul Garcia, a recently sober ex-con who has just served sixteen months in state prison for defrauding Halliburton Industries, his former employer, of $873. Almost forty years old, Paul is highly intelligent but has only been out of New Mexico twice. He has no information. With Catt's help, he makes plans to attend UCLA, only to be arrested on a ten-year-old bench warrant en route. Caught in the nightmarish Byzantine world of the legal system, Catt and Paul's empathic attempts to save each other's lives seems doomed to dissolve. Summer of Hate is a novel about flawed reciprocity and American justice."